How to Identify the Indications for Early Intervention in Acute Necrotizing Pancreatitis Patients: A Long-Term Follow-Up Study - Lu, Jiongdi; Cao, Feng; Zheng, Zhi; Ding, Yixuan; Qu, Yuanxu; Mei, Wentong; Guo, Yulin; Feng, Yu-Lu; Li, Fei (Frontiers in Surgery, 2022)
Abstract Aim: To explore the indications for early intervention in patients with acute necrotizing pancreatitis (ANP) and evaluate the effect of early intervention on the prognosis of ANP patients. Methods: The clinical data of patients with ANP who underwent general surgery at Xuanwu Hospital of Capital Medical University from January 1, 2014, to December 31, 2020, were collected retrospectively. The patients were followed-up every 6 months after discharge, and the last follow-up date was June 30, 2021. Results: A total of 98 patients with ANP were included in the study. They were divided into an early group (n= 43) and a delayed group (n = 55) according to the first percutaneous drainage (PCD) intervention time (≤ 4 weeks or > 4 weeks). Body temperature, inflammatory factor levels, and the number of patients with persistent organ failure (POF) were higher in the early group than in the delayed group. After the minimally invasive intervention, the body temperature and inflammatory factors of the two groups decreased significantly, most patients with POF improved, and the number of patients with reversal of POF in the early group was higher than that in the delayed group. Although the patients in the early group required more surgical intervention than those in the delayed group, there was no significant difference in mortality, incidence of postoperative complications, total length of hospital stay, or operation cost between the two groups. During long-term follow-up, there was no significant difference in the incidence of short-term and long-term complications and overall survival between the two groups. Conclusions: Compared to patients in the delayed group, early intervention did not affect the prognosis of patients with ANP. It may be more suitable for patients with ANP with deterioration (such as POF or infected pancreatic necrosis [IPN]).